How Do School Facilities Affect School Quality? Case Study in Vocational High School at Pati, Indonesia - Tiara Octavia, Eka; ., Ismiyati; Sholikah, Mar’atus (KnE Social Sciences, 2020)
The study aims to determine about how does school facilities affect school quality at vocational high school in Pati, Central Java, Indonesia. The approach and methods used in the study was evaluation research using a discrepancy model. The data were collected by observation, interview, and documentation. Meanwhile, the analysis used interactive model by Milles and Huberman. The results showed that the school facility at vocational high school in Pati is up to standard of Regulation of National Education Minister Number 40 Year 2008. The value of school infrastructure is 72.5% or adequate category, while school facility is 84.3% or adequate category. School facilities become one of the factors in supporting student learning achievement and teacher performance. Therefore, learning achievements can be improved through improved the school facilities. Thus, it is able to improve the school quality. Keywords: school facilities, discrepancy model, school quality, learning achievement